Antroponyms of Čekiškiečiai - Bačiūnaitė, Lina; Mickienė, Ilona (Respectus Philologicus, 2001)
The concept of a sign is better applied to proper words than to common ones, as they reveal the most general relation of its denomination with a person, a geographic object, a piece of art, etc. The surnames descending from nicknames bear certain associations as well as emotional shade.Lithuanian anthroponymic system has passed a long way since the naming of a person by one personal proper name developed to the present day naming by a name and a surname. The result of this change is revealed in the 18th century anthroponymy.Even today linguists cannot come to the point with regard to the definition of a surname, though they agree on its inheritability and belonging to one family.There are 293 surnames registered in Čekiškė today. Referring to Church archives, the oldest surnames are the following: Astrauskas, Bakanauskas, Kochanauskas, Maziliauskas. Lithuanian surnames were formed in the 18th century. Church archives prove that in the course of the centuries, the surnames were written in Polish (1848–1853), Russian (1855–1863) and German (1917–1923). Each of these languages had influenced certain changes in suffixes and endings of the surnames. In such a way the surnames began representing the nation.Few inhabitants of Čekiškė have surnames descending from old Lithuanian two-stem personal proper names: Draudvilas, Gedminas and Kontrimas. A larger group of surnames includes those derived from the names of the saints: Lukoševičius, Morkus, Simonavičius.The surnames of patronymic and nickname formation are exceptionally rare.With regard to origin, the largest group is made up of Slavic surnames. This is revealed not only by the Slavic suffixes -avičius, -evičius but also by the Slavic root.The influence of Slavic languages upon the Lithuanian surnames took place due to uneducated clerks, though in many cases it appeared as an outcome of the conscious canonization of the Polish tongue. The surnames of the Germanic origin make up just 4% in Čekiškė.Due to dialectal peculiarities (the vowel shortening), the surnames had several variants: Kocanauskas – Kukanauskas, Olendra – Ulendra.As women did not take an active part in public life, their surnames appear in the official sources very late. In many cases, they were spelled with masculine endings: Marianna Balsis. Magdalena Rebždis.In the register of deaths of 1945, the surnames are already normed.The surnames reveal all the turnings and trials in the destiny of our nation. The influence of Russification (Russian) and Polonization (Polish) was felt all over the country and especially in Čekiškė, were lived many Polish people.
Keywords: antroponyms; the injluence of the Slavic languages upon Lithuanian surnames; old two-stem person s praper names of patronymic; nonpatronymic and nickname origin